Business Communication in Developing the Halal Tourism Industry - Kunaifi, Aang; Syam, Nur (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
Communication is part of marketing activities, to introduce a business to the public. Through good communication, it is hoped that the company will get people's attention to take advantage of services or consume a product. The better the communication, the more maximum public attention and interest in the services or products offered. This paper aims to determine the effectiveness of business communication in developing halal tourism. This article was written by analyzing information from primary sources, namely tourism managers, community leaders, and Ulama councils that were directly related to the case of the unilateral closure of a tourist destination and the phenomenon of the development of the tourism industry in Pamekasan. The results of this study indicate that there is ineffective communication between managers and community leaders, in the form of errors in identifying parties who have real influence. Acceptance of public figures or leaders through effective business communication ensures the smooth development of halal tourism because the community will support it as a form of resignation to community leaders.